(untitled) (Journal of Educational Sciences, 2023)
Modern challenges require a dynamic transformation of the education management system. The purpose of the article is to describe the main approaches in the analysis of information and management competence of the heads of structural divisions of a modern university. The methodological basis of the study is the results-oriented management methodology, a process-oriented approach, a systematic approach in management, as well as the provisions of synergetic, acmeological, moderative and level approaches. The article discusses the features of the theoretical aspects of the study of information management competence of managers, general criteria and factors for the development of information management competence. The result of the study is a theoretical substantiation and comparative analysis of the concepts of information and management competence of the heads of structural divisions of the university. The scientific novelty lies in the fact that the material of the article contributes to the development of management theory, educational management, the system of professional development for heads of structural divisions of universities. 43 heads of structural subdivisions of the Al-Farabi Kazakh National University took part in the pilot study. The practical significance of the article is related to the possibility of using the collected data in improving the training of a new generation of higher education leaders with a high level of professionalism, competence, information and management culture. Key words: information culture, information worldview, information competence, information literacy, information and management competence of the head of the structural unit of the university, manager of the educational institution.